Alih Kode Dan Campur Kode Dalam Video Blogger Suki Suka Japan - Cahyanti, Putu Wiwin; Andry Anita Dewi, Ni Made (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 2 (2022), 2022)
This research is entitled "Code-switching and code-mixing in the video blogger Suki Suka Japan". The purpose of this research is to represent the factors that cause and types of the process of code-switching and code-mixing on the video blogger Suki Suka Japan. This study uses three theories, namely the theory of code-switching (Wardhaugh); code-mixing theory (Hoffmann), and the theory that causes code-mixing (Weinrich). The research method is discriptive analysis with an approach using listening techniques and note-taking techniques. Data were analyzed using agih and tapping methods as well as informal. The results showed that there were 3 types of metaphorical code-switching data and two types of situational code-switching data. In the code-mixing data, there are 2 pieces (code-mixing in sentences), 3 pieces (mixing code in lexical), and 1 pieces (mixing code in phonological).